Controlling w teorii i w praktyce - Gorczyński, Kazimierz (Controllership in Theory and Practice, 2006)
The controllership as an instrument of management is a modern method, which at first had been implemented in corporate practice, and then started to be a subject of academic research. The aim of the article is to compare theoretical understanding of controllership with practice of corporations. Firstly there is a history of controllership, as a management concept, shortly described. The second part presents different definitions, schools and classifications of controllership, which can be found in the academic literature. At the end the theory is compared with practical aspects of the controllership implementation treated as a corporate managerial system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 95-103